Indonesia's Strategy in Maritime Defense Diplomacy to the State FPDA members (Malaysia, Singapore, Australia, New Zealand, and United Kingdom) - Susilowati, Ida; Maulida, Savira; Hartadi, Najla Aulia (ADALAH, 2024)
Indonesia has long established cooperative and diplomatic relations with the five FPDA member countries. However, this relationship still arouses a sense of mistrust from all parties with the emergence of issues and tensions in diplomatic relations. The presence and establishment of FPDA itself is also one of the reasons to "balance Indonesia". This is a gap for better cooperation between Indonesia and FPDA member countries. The problem in this study is how the pattern of maritime defense diplomacy cooperation and Indonesia's interests towards FPDA member countries using the theory of maritime defense diplomacy as well as the concept of maritime security and national interests. This research uses qualitative methods in a descriptive-analytical manner. The results of the research that the role of multilateral cooperation in Indonesia's maritime defense diplomacy has been actively prioritized by building a sense of trust (CBM), by implementing 5 patterns of defense diplomacy to FPDA countries, Indonesia's interests in FPDA countries, namely: building FPDA trust in Indonesia, increasing cooperation in the maritime sector, reducing the issue of Papuan separatism, and maintaining ASEAN centrality.